PENGARUH MODEL PEMBELAJARAN TALKING STICK BERBASIS WORDWALL TERHADAP HASIL BELAJAR SISWA PADA PELAJARAN IPAS KELAS V SD NEGERI 004 BALAM SEMPURNA - Elsa Romauli Br. Samosir; Patri Janson Silaban; Jhonas Dongoran; Bogor Lumbanraja; Eka Kartika Silalahi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of the Talking stick learning model based on Wordwall on student learning outcomes in the Science lesson on the material "My dear earth, my poor earth" V SD Negeri 004 Balam Sempurna in the 2024/2025 Academic Year. The research method used is an experimental method with a quantitative research type. To obtain data, a test instrument of 35 questions and a questionnaire of 27 items are required. The number of research samples was 23 students using a purposive sampling technique. To determine the initial abilities of students, the researcher conducted a Pretest with an average score of 69.56 which was included in the sufficient category. The results of the Pretest have increased from the results of the Posttest given previously with an average score reaching 87.39 with a very good category. It can be said that the level of success of student learning outcomes using the Talking stick model based on Wordwall has increased and has an effect with a strong category as evidenced by the results of the correlation coefficient test calculation obtained the results of r_count ≥〖 r〗_table with results of 0.755 ≥ 0.413. Next, hypothesis testing compares the value of t_count ≥ t_table. The value of t_count = 11.943 while t_table = 1.714 is obtained. Because t_count ≥ t_table (11.943 ≥ 1.714) then Ha is accepted and Ho is rejected. Through the t-test, it can be concluded that there is a significant positive influence between the Talking stick learning model based on Wordwall (X) on student learning outcomes (Y).